The effect of accuracy constraints on lower limb joint contributions during the instep soccer kick - Lunn, D. E.; Spears, I. (ISBS Proceedings Archive (Michigan), 2021)
The aim of this study was to quantify the effect of accuracy constraints on the kinematics of the soccer instep kick with specific reference to the relative contributions of the segments of the kicking leg. Eight university level soccer players were recruited into the study. Targets of three sizes were positioned and upon a verbal cue the subjects kicked the ball towards the requested target. For each, successful, kick the lower limb 3-dimensional kinematics and relative joint contributions in the local flexion-extension plane immediately prior to impact were recorded. We found foot speeds decreased significantly for the smaller targets. Soccer kicks between the no target and small target significantly increased the contribution of the ankle joint by 24%. This was at the expense of decreases in both the knee (10%) and hip (14%) contributions. Incorporating targets in soccer kicking affects the proximal to distal transition and relative joint contributions of the lower limb.